Molecular, genetic, cellular, and network functions in the spinal cord and brainstem. (26th March 2013) - Stein, Paul S.G.
Abstract : Studies of the model systems of spinal cord and brainstem reveal molecular, genetic, and cellular mechanisms that are critical for network and behavioral functions in the nervous system. Recent experiments establish the importance of neurogenetics in revealing cellular and network properties. Breakthroughs that utilize direct visualization of neuronal activity and network structure provide new insights. Major discoveries of plasticity in the spinal cord and brainstem contribute to basic neuroscience and, in addition, have promising therapeutic implications.